Metal oxidation states in biological water splitting1. Issue 3 (16th March 2015) - Krewald, Vera; Retegan, Marius; Cox, Nicholas; Messinger, Johannes; Lubitz, Wolfgang; DeBeer, Serena; Neese, Frank; Pantazis, Dimitrios A.
<x xml:space="preserve">Abstract</x> A central question in biological water splitting concerns the oxidation states of the manganese ions that comprise the oxygen-evolving complex of photosystem II.